2018
DOI: 10.1016/j.mjafi.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia in children with cyanotic congenital heart disease and effect on cyanotic spells

Abstract: The prevalence of IDA in children with CCHD was found to be high. Iron-deficient group had an increased frequency of cyanotic spells as compared to the non-deficient group, which was statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
3
20
1
Order By: Relevance
“…There is a paucity of literature discussing iron deficiency among children with CCHD and these studies have shown varying results. Our result is similar to prevalence rate found by Mukherjee S et al 16 In 1990, West et al, have demonstrated than more than one-third of patients with CCHD had iron deficiency. 17 In another study done by Olcay L et al, the prevalence of IDA was found to be 52.2%.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There is a paucity of literature discussing iron deficiency among children with CCHD and these studies have shown varying results. Our result is similar to prevalence rate found by Mukherjee S et al 16 In 1990, West et al, have demonstrated than more than one-third of patients with CCHD had iron deficiency. 17 In another study done by Olcay L et al, the prevalence of IDA was found to be 52.2%.…”
Section: Resultssupporting
confidence: 93%
“…4 In the study conducted by Mukerjee S et al, the frequency of cyanotic spells in the iron deficient group was 25% and association between iron deficiency anemia and cyanotic spells were found to be statistically significant (p value-0.042). 16 Children with IDA had eight times the risk of having cyanotic spells compared to the children who were not iron deficient highlighting the need of iron supplementation in children with cyanotic CHD…”
Section: Resultsmentioning
confidence: 99%
“…Iron, B12, and folate deficiencies are considered the major reason behind the deficiency anemias. Mukherjee et al reported the prevalence of iron deficiency in about 47% of his study subjects (4). The primary reason behind the coagulopathy is possibly endothelial dysfunction, platelet activation, and hemostatic abnormalities.…”
Section: Metabolic and Endocrinological Comorbiditiesmentioning
confidence: 90%
“…Both cyanotic and acyanotic congenital heart diseases have risks of iron reserves depletion in the body. The study by Mukherjee et al, (2018) showed 5 to 10 patients with cyanotic CHDs suffered from iron deficiency (Mukherjee et al, 2018). Meanwhile, Binh et al, (2018) reported 77.8% and 87.2% cyanotic and acyanotic CHD patients respectively suffered from the decrease in iron levels in the blood.…”
Section: Introductionmentioning
confidence: 98%